Quality Control Analysis on MPGG Products Using Six Sigma DMAIC Method at PT Nugraha Potong Tekuk - Egga Jerri Indri Saputri; Ahmad Zada Hilmi Syifa (International Journal of Mechanical, Industrial and Control Systems Engineering, 2025)
Product quality is a key factor in enhancing a company's competitiveness. PT Nugraha Potong Tekuk, a producer of MPGG products, experienced a significant increase in the defect rate, reaching 11% of total production during the period from June 24 to July 16, 2024. This study aims to analyze the defect rate, identify the main causes, and provide improvement recommendations. The study follows the Six Sigma methodology, including the Define, Measure, Analyze, Improve, and Control (DMAIC) phases. Based on P-Chart analysis, the production process is within statistical control limits, but the defect rate still requires improvement. Two main types of defects were identified: unevenness and size defects, each accounting for 50% of the total defects. Fishbone diagram analysis revealed four main contributing factors: people, machines, materials, and environment. The people factor includes lack of operator skills and operator fatigue, while the machine factor covers worn-out tools and uncalibrated measuring instruments. The material factor is related to low-quality raw materials, and the environmental factor includes poor lighting and unstable work surfaces. Improvement recommendations include operator training, routine machine maintenance, quality control of raw materials, and improvement of the work environment. This study is expected to help PT Nugraha Potong Tekuk enhance product quality, reduce defect rates, and maintain competitiveness in the market.